Metod postroeniya dbykhmernogo taksonomicheskogo prostranstva dlya klassifikatsii igr i vidov sporta - Lebed, F. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The one of the important problems of the sport's theory is the logically balanced classification of games and sports. There are many examples of classifications simultaneously based on too many logical criterions. This approach is understandable because researchers tried to generalize as much as possible of games features, on the one hand. On the other hand, it is logically uncorrectable: to base simple "linear" classification on more than one criterion. The suggested by the author the method of the construction of two-measured taxonomic space as the way of the correct classification can become the successful decision of the conflict situation drawn here. The author means the contradiction between the multi-face characters of games and sports against to mono-face character of the logically correct classification.